The Application of Blockchain Technology in International Financial Management: Opportunities and Challenges - Noch, Muhammad Yamin (Manunggal Halim Jaya, 2024)
Blockchain technology has emerged as a disruptive force in the realm of global finance, offering the promise of enhanced efficiency, transparency, and security. This paper provides a comprehensive examination of the applications, opportunities, and challenges presented by blockchain in the context of international financial management. The decentralized ledger system of blockchain holds significant potential for automating processes and improving credit identification in Islamic finance, yet it faces obstacles such as regulatory uncertainty and interoperability issues in traditional banking systems. Despite these challenges, blockchain has the capacity to streamline cross-border payments, digitize trade finance operations, and revolutionize cross-border remittances. However, scalability concerns and regulatory ambiguities pose significant hurdles to widespread adoption and implementation. Considering these challenges, collaboration and innovation are essential to unlocking the full transformative potential of blockchain in reshaping the landscape of global finance. By addressing regulatory uncertainties, enhancing scalability, and fostering collaboration between industry stakeholders and policymakers, blockchain technology can pave the way for a more efficient, transparent, and inclusive international financial ecosystem.